Efficacy and Safety of Pleural Cryobiopsy vs. Forceps Biopsy for Evaluation of Undiagnosed Pleural Effusion: A Systematic Review and Meta-Analysis - Giri, Mohan; Dai, Haiyun; Guo, Shuliang; Li, Yishi; He, Lin; Zhuang, Rongjuan (Frontiers in Medicine, 2022)
Background: Pleural cryobiopsy is a novel technique for the diagnosis of pleural pathologies. However, the safety and feasibility of this modality compared to standard forceps for pleural biopsy has not been fully elucidated. This systematic review and meta-analysis aims to establish the efficacy and safety of cryobiopsy for evaluation of undiagnosed pleural effusion. Methods: For this systematic review and meta-analysis, we searched PubMed, Embase, Scopus, and Web of science databases up to December 16, 2021 to identify relevant articles. We included randomized controlled trials, cohort studies, retrospectives studies and case series that compared pleural cryobiopsy and forceps biopsy. A qualitative assessment was performed using the QUADAS-2 tool. Results: Of the 365 articles identified by our search, 15 studies were eligible for inclusion. The specimen sizes obtained with cryobiopsy were significantly larger compared with forceps biopsy (Standard mean difference 1.16; 95 % CI: 0.51-1.82; P<0.01). Furthermore, the cryobiopsy tissue specimens were deeper (OR 2.68; 95 % CI: 1.39-5.16; P<0.01) and qualitatively better with less crush artifacts (OR 0.06; 95 % CI: 0.01-0.26; P<0.01). There was no significant difference in diagnostic yield (OR 1.32; 95 % CI: 0.79-2.21; P=0.29) and mild to moderate bleeding events (OR 1.21; 95 % CI: 0.64-2.29; P=0.57) between pleural cryobiopsy and forceps biopsy. No publication bias was observed among these studies. Conclusions: Compared to flexible forceps biopsy pleural cryobiopsy obtained larger and deeper tissue specimens with less crush artifacts but does not show superiority for diagnostic yield. Further studies are still needed to verify these findings.